Characteristics of concrete containing crushed glass and ceramic waste as fine aggregate material - Adnan, Suraya Hani; Lee, Tze Hui; Kamarulzaman, Nurul Amirah (Penerbit UTHM, 2017)
Construction industry is considered as major stimulant to Malaysia economy. However, it also generates waste from the construction activities [1]. Concrete is the most favourite choice used in construction industry because of its basic ingredients are easily to find, little maintenance service, easily to handle, most economical material, good in compression, durable and good fire resistance. Furthermore, there is scarcity of natural sources like coarse aggregate [2]. Revolutions in seeking new material for construction materials never stop. Human being starts to realise that the fact of environment impacts due to the poor management of waste product produced by industries in this whole world. The increasingly wide spectrum of environmental issues makes it necessary to adopt preventive approach to the link between manufacturing activities and environment quality. Therefore, a better and more sustainable initiative should be applied such as recycling the waste products and reuse the by-products in construction industries. Nowadays, there are many research and development in Malaysia about the construction materials which are made from crushed glasses, ceramic waste and even plastic as well as polystyrene. This study was conducted to determine the density and the compressive strength test of the concrete with crushed glass and ceramic waste replacement as well as the water absorption test between the concrete made of crushed glass and ceramic waste. The colour of the waste material is not a consideration factor in this study. The grade of the concrete produced was Grade 25 and the testing was conducted at 7 days and 28 days, respectively.